Distributed adaptive consensus protocols for linear multi‐agent systems over directed graphs with relative output information. Issue 5 (9th January 2018) - Lv, Yuezu; Li, Zhongkui; Duan, Zhisheng
Abstract : This study is concerned with the fully distributed output feedback consensus protocol design problem for multi‐agent systems with general linear dynamics over directed graphs. The authors propose new distributed observer‐based adaptive consensus protocols to achieve consensus for strongly connected directed graphs or leader–follower graphs. Different from the existing adaptive output feedback consensus protocols, which either depend on the absolute output information of each agent and its neighbours or are not fully distributed, the protocols designed in this study relying on only relative output information of neighbouring agents, can be implemented in a fully distributed way.